Climate Intervention in an Earth Systems Science Framework: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
To consider how an Earth system science approach can inform research on climate intervention, The National Academies of Sciences, Engineering, and Medicine held a virtual workshop on June 20-22, 2023 titled Climate Intervention in an Earth Systems Science Framework. Individuals with a wide range of physical, ecological, and social sciences expertise explored climate interventions within the context of convergent research and the capacities of the National Science Foundation (NSF). The workshop drew on the National Academies report Next Generation Earth Systems Science at the National Science Foundation, which called upon NSF to pursue an Earth systems science initiative that emphasizes research on interconnections and feedback between natural and social processes; focuses on real-world problems; enhances the participation of social, engineering, and data scientists; and strengthens efforts to include diverse perspectives in research.
Keywords: Environment and Environmental Studies; Earth Sciences

The Effects of Solar Variability on Earth's Climate: A Workshop Report - National Research Council (The National Academies Press, 2012)
On September 8-9, 2011, experts in solar physics, climate models, paleoclimatology, and atmospheric science assembled at the National Center for Atmospheric Research (NCAR) in Boulder, Colorado for a workshop to consider the Sun's variability over time and potential Sun-climate connections.While it does not provide findings, recommendations, or consensus on the current state of the science, The Effects of Solar Variability on Earth's Climate: A Workshop Report briefly introduces the primary topics discussed by presenters at the event. As context for these topics, the summary includes background information on the potential Sun-climate connection, the measurement record from space, and potential perturbations of climate due to long-term solar variability. This workshop report also summarizes some of the science questions explored by the participants as potential future research endeavors.
Keywords: Earth Sciences; Space and Aeronautics

Climate Security in South Asia: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The South Asia region presents a confluence of major climate impacts and key security issues. From a weather and climate standpoint, the region experiences a wide range of hazards, such as the recent heatwaves, droughts, storms, and floods that have upended the lives and livelihoods of millions of people. From a demographic and socioeconomic standpoint, the region is experiencing rapid transformations and progress, even as fundamental challenges such as poverty and inequality persist. From a security standpoint, the region is the setting for a range of social and political dynamics that impact U.S. interests, including conflict at national and subnational levels; regional rivalries; and the imprint of global geopolitics. On October 26-27, 2022, the National Academies of Sciences, Engineering, and Medicine, under the auspices of the National Academies Climate Security Roundtable, convened a workshop to explore climate security in South Asia. Over two days, workshop participants considered some of the underlying climate, development, and geopolitical dynamics at play in the South Asia region; explored a set of historical case studies and future scenarios for climate change and security in South Asia; and they considered the available tools for analysis and forecasting climate-related risks. This publication summarizes the presentations and discussion of the workshop.
Keywords: Environment and Environmental Studies

Climate Security in Central America: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
To advance a systems understanding of climate-related security risks in the Central America region, the National Academies of Sciences, Engineering, and Medicine convened a workshop titled Climate Security in Central America on May 3-4, 2023. The workshop was held under the auspices of the National Academies Climate Security Roundtable. Over two days, workshop participants considered some of the underlying environmental, social, economic, and political dynamics at play in Central America; they explored indicators and pathways for climate-related security risks in the region; and they considered the available tools for analyzing and forecasting these risks. This publication summarizes the presentations and discussion of the workshop.
Keywords: Environment and Environmental Studies; Conflict and Security Issues

Review of the Federal Strategy for Nanotechnology-Related Environmental, Health, and Safety Research - National Research Council (The National Academies Press, 2009)
This new book from the National Research Council finds serious weaknesses in the government's plan for research on the potential health and environmental risks posed by nanomaterials, which are increasingly being used in consumer goods and industry. An effective national plan for identifying and managing potential risks is essential to the successful development and public acceptance of nanotechnology-enabled products.
Keywords: Engineering and Technology; Health and Medicine; Environment and Environmental Studies

Opportunities and Challenges for Digital Twins in Atmospheric and Climate Sciences: Proceedings of a Workshop—in Brief - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The digital twin is an emerging technology that builds on the convergence of computer science, mathematics, engineering, and the life sciences. Digital twins have the potential to revolutionize atmospheric and climate sciences in particular, as they could be used, for example, to create global-scale interactive models of Earth to predict future weather and climate conditions over longer timescales. On February 1-2, 2023, the National Academies of Sciences, Engineering, and Medicine hosted a public, virtual workshop to discuss characterizations of digital twins within the context of atmospheric, climate, and sustainability sciences and to identify methods for their development and use. Workshop panelists presented varied definitions and taxonomies of digital twins and highlighted key challenges as well as opportunities to translate promising practices to other fields. The second in a three-part series, this evidence-gathering workshop will inform a National Academies consensus study on research gaps and future directions to advance the mathematical, statistical, and computational foundations of digital twins in applications across science, medicine, engineering, and society.
Keywords: Earth Sciences; Computers and Information Technology; Math, Chemistry, and Physics; Engineering and Technology

Assessment of Commercial Space Platforms for Earth Science Instruments: Report Series—Committee on Earth Science and Applications from Space - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Space-based Earth observations enable global observations of the land surface, biosphere, solid Earth, atmosphere, cryosphere, and oceans. Earth observations from space, combined with data acquired from in situ and ground-based instruments, help scientists understand the components of the Earth system and their interactions and enable wide-ranging applications, including forecasts of weather and air quality, projections of future climate, management of natural resources, ecological forecasting, disaster management, drought and wildfire prediction, and the mapping and prediction of vector borne/animal diseases. At the request of NASA Earth Science Division, this report assesses the potential use of a proposed multi-user, robot-tended, uncrewed commercial space platform as a potential host for a large number of Earth remote sensing instruments. Assessment of Commercial Space Platforms for Earth Science Instruments evaluates the utility and practicality of a platform in a Sun-synchronous orbit, capable of hosting 20 or more instruments.
Keywords: Space and Aeronautics

Next Generation Earth Systems Science at the National Science Foundation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The National Science Foundation (NSF) has played a key role over the past several decades in advancing understanding of Earth's systems by funding research on atmospheric, ocean, hydrologic, geologic, polar, ecosystem, social, and engineering-related processes. Today, however, those systems are being driven like never before by human technologies and activities. Our understanding has struggled to keep pace with the rapidity and magnitude of human-driven changes, their impacts on human and ecosystem sustainability and resilience, and the effectiveness of different pathways to address those challenges. Given the urgency of understanding human-driven changes, NSF will need to sustain and expand its efforts to achieve greater impact. The time is ripe to create a next-generation Earth systems science initiative that emphasizes research on complex interconnections and feedbacks between natural and social processes. This will require NSF to place an increased emphasis on research inspired by real-world problems while maintaining their strong legacy of curiosity driven research across many disciplines – as well as enhance the participation of social, engineering, and data scientists, and strengthen efforts to include diverse perspectives in research.
Keywords: Earth Sciences

Making Climate Assessments Work: Learning from California and Other Subnational Climate Assessments: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Climate assessment activities are increasingly driven by subnational organizations—city, county, and state governments; utilities and private companies; and stakeholder groups and engaged publics—trying to better serve their constituents, customers, and members by understanding and preparing for how climate change will impact them locally. Whether the threats are drought and wildfires, storm surge and sea level rise, or heat waves and urban heat islands, the warming climate is affecting people and communities across the country. To explore the growing role of subnational climate assessments and action, the National Academies of Sciences, Engineering, and Medicine hosted the 2-day workshop on August 14-15, 2018. This publication summarizes the presentations and discussions from the workshop.
Keywords: Environment and Environmental Studies

Lessons Learned in the Implementation of NASA's Earth Venture Class - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The NASA Science Mission Directorate/Earth Science Division's (SMD/ESD's) Earth Venture (EV) is a program element within the Earth System Science Pathfinder Program. At the request of NASA, this report examines the Earth Venture Instrument (EV-I) and Earth Venture Mission (EV-M) elements of Earth Ventures and explores lessons learned in the more than 10 years since selection of the first EV mission, including a review of the foundational principles and approaches underlying the program.
Keywords: Space and Aeronautics

Leveraging Commercial Space for Earth and Ocean Remote Sensing - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Within the past decade an ever-growing number of New Space organizations have emerged that are unencumbered by legacy practices and constraints. By reimagining, creating, and continuously improving SmallSat space technology a new and growing space ecosystem is now in place that is capable of serving a broad stakeholder community of both traditional users and new or nontraditional users.
Keywords: Engineering and Technology

Machine Learning and Artificial Intelligence to Advance Earth System Science: Opportunities and Challenges: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The Earth system - the atmospheric, hydrologic, geologic, and biologic cycles that circulate energy, water, nutrients, and other trace substances - is a large, complex, multiscale system in space and time that involves human and natural system interactions. Machine learning (ML) and artificial intelligence (AI) offer opportunities to understand and predict this system. Researchers are actively exploring ways to use ML/AI approaches to advance scientific discovery, speed computation, and link scientific communities. To address the challenges and opportunities around using ML/AI to advance Earth system science, the National Academies convened a workshop in February 2022 that brought together Earth system experts, ML/AI researchers, social and behavioral scientists, ethicists, and decision makers to discuss approaches to improving understanding, analysis, modeling, and prediction. Participants also explored educational pathways, responsible and ethical use of these technologies, and opportunities to foster partnerships and knowledge exchange. This publication summarizes the workshop discussions and themes that emerged throughout the meeting.
Keywords: Computers and Information Technology; Earth Sciences

Airborne Platforms to Advance NASA Earth System Science Priorities: Assessing the Future Need for a Large Aircraft - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The National Aeronautics and Space Administration (NASA) and other U.S. science research agencies operate a fleet of research aircraft and other airborne platforms that offer diverse capabilities. To inform NASA's future investments in airborne platforms, this study examines whether a large aircraft that would replace the current NASA DC-8 is needed to address Earth system science questions, and the role of other airborne platforms for achieving future Earth system science research goals.
Keywords: Space and Aeronautics; Earth Sciences

National Security Implications of Climate Change for U.S. Naval Forces - National Research Council (The National Academies Press, 2011)
In response to the Chief of Naval Operations (CNO), the National Research Council appointed a committee operating under the auspices of the Naval Studies Board to study the national security implications of climate change for U.S. naval forces. In conducting this study, the committee found that even the most moderate current trends in climate, if continued, will present new national security challenges for the U.S. Navy, Marine Corps, and Coast Guard. While the timing, degree, and consequences of future climate change impacts remain uncertain, many changes are already underway in regions around the world, such as in the Arctic, and call for action by U.S. naval leadership in response. The terms of reference (TOR) directed that the study be based on Intergovernmental Panel on Climate Change (IPCC) scenarios and other peer-reviewed assessment. Therefore, the committee did not address the science of climate change or challenge the scenarios on which the committee's findings and recommendations are based. National Security Implications of Climate Change for U.S. Naval Forces addresses both the near- and long-term implications for U.S. naval forces in each of the four areas of the TOR, and provides corresponding findings and recommendations. This report and its conclusions are organized around six discussion areas—all presented within the context of a changing climate.
Keywords: Conflict and Security Issues; Transportation and Infrastructure

Testing and Validating the Staffing Methodology for the Veterans Health Administration: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
On June 21-22, 2021, the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on behalf of the Veterans Health Administration (VHA). This was the final in a series of workshops undertaken as part of a consensus study to prepare a resource planning and staffing methodology for VHA Facility Management (Engineering) Programs. In its consensus study report, the committee determined that the implementation of a staffing methodology is necessary for the VHA - both in response to congressional mandates for workforce projections and for the purpose of making better, data-informed staffing decisions; thus, the VHA began to develop an engineering staffing tool. The purpose of this workshop was to provide an update on the current status of and future opportunities for the VHA staffing tool, examine benchmarking for facilities, and discuss implementation. This publication summarizes the presentations and discussion of the workshop.
Keywords: Behavioral and Social Sciences

Issues in the Integration of Research and Operational Satellite Systems for Climate Research: Part II. Implementation - National Research Council (The National Academies Press, 2000)
This is the second of two Space Studies Board reports that address the complex issue of incorporating the needs of climate research into the National Polar-orbiting Operational Environmental Satellite System (NPOESS). NPOESS, which has been driven by the imperative of reliably providing short-term weather information, is itself a union of heretofore separate civilian and military programs. It is a marriage of convenience to eliminate needless duplication and reduce cost, one that appears to be working. The same considerations of expediency and economy motivate the present attempts to add to NPOESS the goals of climate research. The technical complexities of combining seemingly disparate requirements are accompanied by the programmatic complexities of forging further connections among three different agencies, with different mandates, cultures, and congressional appropriators. Yet the stakes are very high, and each agency gains significantly by finding ways to cooperate, as do the taxpayers. Beyond cost savings, benefits include the possibility that long-term climate observations will reveal new phenomena of interest to weather forecasters, as happened with the El Niño/Southern Oscillation. Conversely, climate researchers can often make good use of operational data. Necessity is the mother of invention, and the needs of all the parties involved in NPOESS should conspire to foster creative solutions to make this effort work. Although it has often been said that research and operational requirements are incommensurate, this report and the phase one report (Science and Design) accentuate the degree to which they are complementary and could be made compatible. The reports provide guidelines for achieving the desired integration to the mutual benefit of all parties. Although a significant level of commitment will be needed to surmount the very real technical and programmatic impediments, the public interest would be well served by a positive outcome.
Keywords: Earth Sciences; Space and Aeronautics

Opportunities and Challenges for Using Digital Health Applications in Oncology: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Digital health encompasses a broad array of tools and strategies with the goals of advancing research, increasing health care access and quality, and making care more personalized. It encompasses health content, digital health interventions, and digital applications, such as communication tools connecting patients and clinicians (e.g., secure email in the patient portal, text, chat, video visit), remote monitoring tools, clinical decision support tools, and systems for exchanging health information. Patient-facing tools, tools for clinicians, and systems to facilitate research and care improvement are all part of this diverse landscape, and each raises unique opportunities and potential challenges. To examine key policy issues for the effective and safe development, implementation, and use of digital health technologies in oncology research and care, the National Cancer Policy Forum of the National Academies of Sciences, Engineering, and Medicine held a virtual workshop in collaboration with the Forum on Cyber Resilience. The workshop, Opportunities and Challenges for Using Digital Health Applications in Oncology, held on July 13-14, 2020, convened a broad group of experts, including clinicians and researchers; patient advocates; and representatives of federal agencies, health professional societies, health care organizations, insurers, and the pharmaceutical and health technology industries. Many workshop speakers found the opportunities presented by digital health tools to be particularly compelling for oncology; however, capitalizing on these opportunities necessitates careful attention to the design, implementation, and use of digital health technologies. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Computers and Information Technology

Innovation in Electronic Health Records for Oncology Care, Research, and Surveillance: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Electronic Health Records (EHRs) are used across a wide variety of activities in cancer care and cancer research, including communication among health care team members and patients, clinical documentation and treatment planning, patient safety and quality improvement, scheduling and billing, as well as clinical research and disease surveillance activities. On February 28 and March 1, 2022, the National Cancer Policy Forum and the Computer Science and Telecommunications Board of the National Academies of Sciences, Engineering, and Medicine hosted a public workshop to examine opportunities to improve patient care and outcomes through collaborations to enhance innovation in the development, implementation, and use of EHRs in oncology care, research, and surveillance. This Proceedings of a Workshop summarizes the presentations and discussions that took place at the workshop.
Keywords: Health and Medicine; Computers and Information Technology

Ensuring the Climate Record from the NPP and NPOESS Meteorological Satellites (The National Academies Press, 2000)
Keywords: Space and Aeronautics; Environment and Environmental Studies

Issues in the Integration of Research and Operational Satellite Systems for Climate Research: Part I. Science and Design - National Research Council (The National Academies Press, 2000)
Currently, the Departments of Defense (DOD) and Commerce (DOC) acquire and operate separate polarorbiting environmental satellite systems that collect data needed for military and civil weather forecasting. The National Performance Review (NPR) and subsequent Presidential Decision Directive (PDD), directed the DOD (Air Force) and the DOC (National Oceanic and Atmospheric Administration, NOAA) to establish a converged national weather satellite program that would meet U.S. civil and national security requirements and fulfill international obligations. NASA's Earth Observing System (EOS), and potentially other NASA programs, were included in the converged program to provide new remote sensing and spacecraft technologies that could improve the operational capabilities of the converged system. The program that followed, called the National Polar-orbiting Operational Environmental Satellite System (NPOESS), combined the follow-on to the DOD's Defense Meteorological Satellite Program and the DOC's Polar-orbiting Operational Environmental Satellite (POES) program. The tri-agency Integrated Program Office (IPO) for NPOESS was subsequently established to manage the acquisition and operations of the converged satellite. Issues in the Integration of Research and Operational Satellite Systems for Climate Research analyzes issues related to the integration of EOS and NPOESS, especially as they affect research and monitoring activities related to Earth's climate and whether it is changing.
Keywords: Earth Sciences; Space and Aeronautics